Removal and safe reuse of highly toxic allyl alcohol using a highly selective photo-sensitive metal–organic framework. Issue 7 (26th November 2015) - Gong, Le Le; Feng, Xue Feng; Luo, Feng; Yi, Xian Feng; Zheng, An Min
Abstract : By means of a MOF platform and photo-assistant adsorption technique, the removal and reuse of highly toxic allyl alcohol can be achieved. This is mainly based on a reversible asymmetric [2 + 2] cycloaddition inside a MOF. Abstract : Herein, we report a facile and green approach to remove, convert and even release highly toxic allyl alcohol inside a MOF. The MOF used here, namelyECIT-20, barely adsorbs allyl alcohol under ambient conditions, whereas a sharp increase up to 90 mg g −1 (1.03 mol mol −1 ) under UV (297 nm) irradiation is observed, giving an ultra-big photo-switching behavior of more than 19 times. Thermogravimetric analysis, infrared spectroscopy, and 1 H MAS plus 13 C CPMAS solid-state NMR spectroscopy showed that a host–guest photochemical [2 + 2] reaction followed by the formation of asymmetric cyclobutanes is responsible for this unique photo-switching behavior towards allyl alcohol. The final conversion capability by means ofECIT-20 from allyl alcohol to asymmetric cyclobutanes is estimated to be 0.5 mol mol −1, which agrees well with both the structural features and the results from density functional theory (DFT) calculations. Moreover, the reuse of this MOF material is also facile and even after four cycles, excellent photo-switching performance towards allyl alcohol could be well maintained. This indicates that the highly promising material ofECIT-20 is suitable for the green removal and safe reuse of highly toxic allyl alcohol.